2019
DOI: 10.36570/jduhs.2019.3.693
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange versus intravenous immunoglobulin in children with Guillain Barré syndrome

Abstract: Objective: To compare the outcome of plasma exchange versus intravenous immunoglobulin among children with Guillain Barre Syndrome. Methods: A comparative experimental study was conducted at department of Pediatrics, National Institute of Child Health, Karachi from August 2016 to February 2017. All patients of age ranged from 2-15 years of either gender having duration of Guillain Barre Syndrome not more than 14 days were included. The children were divided into plasma exchange or intravenous immunoglobulin gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our meta-analysis has also shown that the hospitalization duration of GBS patients tends to be shorter when IVIG is used as the treatment option for GBS; however, the difference compared with PE is not statistically different. Conversely, evidence in some studies has shown that patients receiving IVIG treatment can have significantly shorter hospital stays [ 16 , 18 ]. This short hospital stay can be explained by the fact that IVIG also considerably reduces the time to attain better functional grades for patients with GBS [ 11 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta-analysis has also shown that the hospitalization duration of GBS patients tends to be shorter when IVIG is used as the treatment option for GBS; however, the difference compared with PE is not statistically different. Conversely, evidence in some studies has shown that patients receiving IVIG treatment can have significantly shorter hospital stays [ 16 , 18 ]. This short hospital stay can be explained by the fact that IVIG also considerably reduces the time to attain better functional grades for patients with GBS [ 11 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“… Author ID Participants' characteristics IVIG administration PE administration Outcomes Quality of study Sample, n (men) Age Saad et al2016 [ 14 ] 62 (26) 8.0 ± 4.7 years 0.4 g/kg/day for 5 days 200–250 ml/kg was administered over 7–10 Hospitalization length, mortality and curative effect Fair El-Bayoumi et al,2011 [ 15 ] 41 49–143 months 0.4 g/kg/day for 5 days One volume of PE per day Length of PICU stay, and MV duration Fair Charra et al,2014 [ 16 ] 41 (31) 37.4 ± 9.2 years 0.4 g/kg/day for 5 days 4 PE over 10–14 days Length of ICU stay, and MV duration Fair Kuwabara et al,2001 [ 17 ] 24 (11) NR 400 mg/kg/day for 5 days 50 ml/kg plasma was treated 4–8 times daily. Curative effect Fair Elahi et al,2019 [ 18 ] 78 (47) 6.64 ± 3.06 years 0.4 g/kg/day for 5 days One-volume PE per day Length of PICU stay, and MV duration Poor Tsai et al,2007 [ 19 ] 24 (19) 7–79 years 0.4 mg/kg for 5 days 40–50 ml/kg, 4–8 times Hospitalization length, and Complications Fair Bondi et al,2021 [ 20 ] 70 (38) NR NR NR Length of ICU stay Poor Beydoun et al,2020 [ 21 ] 6586 (3711) NR NR NR Hospitalization length, and mortality and Poor …”
Section: Methodsmentioning
confidence: 99%
“…Thirteen studies assessed the ability to regain independent locomotion/recovery/cure rate: Five studies reported patients with IVIG treatment recovered better and regained independent locomotion earlier than those patients on PE, four studies concluded that both treatments showed no significant difference in recovery or time for regaining independent locomotion, and three studies by [16,17,28].…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Ten studies assessed for need and duration of MV: Five studies reported decreased need and duration of MV in patients who received IVIG, two studies reported no significant difference in need and duration of MV, and the studies by Saad et al and El-Bayoumi et al reported that duration of MV was significantly less in PE group children, whereas the study by Elahi et al reported that mean duration of MV stay was significantly higher among children receiving plasma exchange[16,17,28].Eight studies assessed for length/duration of hospital stay: Five studies reported that the duration of hospital stay was significantly less in the IVIG treatment group, one study by El-Bayoumi et al reported no significant difference in PICU stay among both treatment groups, and a study by Saad et al reported that in children duration of hospital stay was less among PE group, whereas a study by Elahi et al reported that higher length of ICU stay was noted among children receiving plasma exchange…”
mentioning
confidence: 99%
“…TPE outcome in different pediatric disorders have been explored in previous studies. 4 , 5 Our study is focused to evaluate the complications of TPE procedure and its safety in severely ill children admitted in PICU. The study’s secondary aim was to examine several characteristics of TPE patients who experienced any complication and tried to establish association of these complications with age, gender, blood group and diagnosis of the patients.…”
Section: Introductionmentioning
confidence: 99%